CHANGES IN GLYCOSYLATED PROTEINS IN TYPE-2 DIABETIC PATIENTS WITH AND WITHOUT COMPLICATIONS - Gul, Anjuman; Rahman, M. Ataur; Jaleel, Anila (Journal of Ayub Medical College Abbottabad, 2005)
Background: Diabetes mellitus constitutes one of the most important problems in developing and developed countries. Increased glycosylation of various proteins in diabetic patients has been reported by many authors. The present study describes the changes in protein glycosylation in diabetic patients with and without diabetic complication. Methods: The study included one hundred and three subjects. Among them 21 were type 2 diabetic patients without any clinical evidence of chronic diabetic complications, 21 were type 2 diabetic patients with cardiovascular complications, 20 were type 2 diabetic patients with cataract, 20 were type 2 diabetic patients with retinopathy and 21 apparently normal, age, sex and weight matched controls. The patients were selected from Ziauddin Medical University Hospital, Karachi and Jinnah Postgraduate Medical Centre, Karachi. Results: Fasting plasma glucose was increased in all diabetic patients and correlated significantly with glycosylated hemoglobin, glycosylated plasma proteins and serum fructosamine concentrations. There was no significant difference in the levels of fasting plasma glucose, glycosylated plasma proteins, glycosylated hemoglobin, serum fructosamine, hexosamine or sialic acid between diabetic patients with or without chronic complications. Alpha-1 and alpha- 2 globulin fraction were significantly increased in diabetic patients without complications, diabetic patients with cardiovascular complications and diabetic patients with cataract. Albumin was found to be decreased in diabetic patients with cataract while gamma globulin was increased in diabetic patients with cardiovascular complications and diabetic patients with cataract. Conclusions: In uncomplicated diabetic patients alpha-1 and alpha-2 glycoproteins were increased. In diabetic patients with cardiovascular complications alpha-1, alpha-2 and gamma globulin were increased while in diabetic patients with cataract alpha-1, alpha-2 and gamma globulin were increased but serum albumin was significantly decreased. Key words: glycosylated hemoglobin, glycosylated plasma protein, serum fructosamine, sialic acid, hexosamine and total serum proteins.